Antimicrobial stewardship in the neonatal unit reduces antibiotic exposure. (23rd April 2018) - McCarthy, KN; Hawke, A; Dempsey, EM
Abstract: Aim: Antimicrobial stewardship plays an important role in ensuring that the appropriate drug, dose, route and duration are employed to provide adequate treatment while minimising the risks of unnecessary antibiotic use. Surveillance of antibiotic use with prescriber feedback is recommended as a high‐impact stewardship intervention. The aim of this study was to reduce unnecessary antimicrobial use in a neonatal unit. Methods: A prospective audit was performed to assess compliance with antimicrobial guidelines. Following this, educational interventions were applied, electronic prescribing was introduced to the neonatal unit, and re‐audit was performed. The primary outcome was a reduction in days of therapy (DOT). Results: There were 312 neonatal admissions. There was a significant overall reduction in the primary outcome of DOT/1000 patient days from 572 to 417 DOT. This represents a 27% reduction in total antibiotic use. Prolonged antibiotic treatment courses >36 hours in negative sepsis evaluations were reduced from 82 DOT to 7.5 DOT. Similarly, treatment courses greater than five days for culture‐negative sepsis were reduced from 46.5 DOT to 7 DOT. Conclusion: Monitoring antibiotic prescribing data can provide useful insights into the trends of antibiotic use and also inform clinicians of potential areas where antibiotic use may be safely reduced.